APPLICATION OF ACTIVITY INDICATORS IN SLOVAK AGRICULTURAL ENTERPRISES - Zuzana Čierna; Jana Prevužňáková (Polityki Europejskie, Finanse i Marketing)
The article evaluates the development of selected activity indicators in period of years 2004-2011 in Slovak agricultural enterprises. The time horizon represents the period of years after the accession of the Slovak republic into the European Union. From the nature of the agricultural arises its lower activity in comparison with industry. Contrary to other activity indicators which development was worsening during the period, DSO of trade receivables has the improving trend in selected companies in comparison between year 2004 and 2011.